2004
DOI: 10.1016/j.jacc.2004.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of medical treatment with percutaneous closure of patent foramen ovale in patients with cryptogenic stroke

Abstract: Percutaneous PFO closure appears at least as effective as medical treatment for prevention of recurrent cerebrovascular events in cryptogenic stroke patients with PFO. It might be more effective than medical treatment in patients with complete closure and more than one cerebrovascular event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0
11

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(146 citation statements)
references
References 42 publications
4
131
0
11
Order By: Relevance
“…18 -20 Some data also suggest that specific PFO parameters, such as the degree of right-to-left shunting, the presence of atrial septal aneurysm, and PFO tunnel length, may increase the risk for thromboembolic events and may represent the cohort of patients who will receive the greatest benefit from device closure. 21,22 Of the 43 patients referred with the diagnosis of TIA, we suspect that 20 patients had complex MHs with transient neurologic deficits but no headaches. Differentiating between these 2 diagnoses remains a clinical dilemma because transient neurologic deficits such as paresthesia, hemiparesis, or aphasia can occur in patients with complex MHs.…”
Section: Discussionmentioning
confidence: 99%
“…18 -20 Some data also suggest that specific PFO parameters, such as the degree of right-to-left shunting, the presence of atrial septal aneurysm, and PFO tunnel length, may increase the risk for thromboembolic events and may represent the cohort of patients who will receive the greatest benefit from device closure. 21,22 Of the 43 patients referred with the diagnosis of TIA, we suspect that 20 patients had complex MHs with transient neurologic deficits but no headaches. Differentiating between these 2 diagnoses remains a clinical dilemma because transient neurologic deficits such as paresthesia, hemiparesis, or aphasia can occur in patients with complex MHs.…”
Section: Discussionmentioning
confidence: 99%
“…Competing data regarding the reduction of stroke recurrence rate and potential drawbacks including periprocedural vascular complication, new-onset arrhythmias or device failure are still the matter of ongoing debate. Several randomized clinical trials and meta-analyses have not shown clear benefit of this procedure [25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…This advantage was significant in terms of major strokes, which only occurred in the conservative group. It was also significant in the subgroup of patients who had had more than two events before treatment allocation as well as in those who had complete closure at the six month follow up TEE in the device group (Windecker, Wahl & Nedeltchev, 2004).The few randomized trials in this field have, for years, struggled to enroll sufficient numbers of patients, owing to a variety of factors, including off-label device use.…”
Section: Catheter-based Pfo and Asd Closurementioning
confidence: 98%